2014
DOI: 10.3390/molecules19033345
|View full text |Cite
|
Sign up to set email alerts
|

Compounds from Dryopteris Fragrans (L.) Schott with Cytotoxic Activity

Abstract: Abstract:One new coumarin, dryofracoumarin A (1), and eight known compounds 2-9 were isolated from Dryopteris fragrans (L.) Schott. Their structures were established on the basis of extensive spectroscopic data analyses and comparison with reported spectroscopic data. The new compound 1 was determined to be 8-hydroxyl-4-isopropyl-7-methyl-6-methyl-2H-benzopyran-2-one. Two dimers, trans-and cis-3-(3,4-dimethoxyphenyl)-4-[(E)-3,4-dimethoxystyryl]cyclohex-1-ene (compounds 8 and 9), were isolated from the Dryopter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…Dryopteris fragrans was mainly used as a folk medicine at present. It has been found that the main active compounds of D. fragrans have a significant effect on a variety of skin diseases caused by fungi ( Wan et al, 2014 ; Zhao et al, 2014 ; Wang et al, 2015 ; Du et al, 2016 ; Huang et al, 2016 ). Our group isolated a variety of phloroglucinols from the plant, and the activity experiment showed that the phloroglucinols had strong antifungal activity, especially methylphloroglucinol derivatives such as aspidin PB, dryofragin, aspidinol, aspidin BB, aspidin AB, and albicanol, in which the hydroxyl group of methylphloroglucinol is the active group of compounds, and C-2 or C-6 is the active site ( Sun et al, 2013 ; Li et al, 2014 ; Gao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dryopteris fragrans was mainly used as a folk medicine at present. It has been found that the main active compounds of D. fragrans have a significant effect on a variety of skin diseases caused by fungi ( Wan et al, 2014 ; Zhao et al, 2014 ; Wang et al, 2015 ; Du et al, 2016 ; Huang et al, 2016 ). Our group isolated a variety of phloroglucinols from the plant, and the activity experiment showed that the phloroglucinols had strong antifungal activity, especially methylphloroglucinol derivatives such as aspidin PB, dryofragin, aspidinol, aspidin BB, aspidin AB, and albicanol, in which the hydroxyl group of methylphloroglucinol is the active group of compounds, and C-2 or C-6 is the active site ( Sun et al, 2013 ; Li et al, 2014 ; Gao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The backbone of 2 was deduced from the HMBC correlations from methyl ( δ H 2.12) to C-4 ( δ C 162.56), C-5 ( δ C 113.37), and C-6 ( δ C 161.87), and from olefinic proton ( δ H 6.42) to C-1 ( δ C 112.03), C-2 ( δ C 163.37), C-4 ( δ C 162.56), and C-5 ( δ C 113.37). The NMR data of 2 were similar to those of methylphlorbutyrophenon[ 5 ] except for the sugar moiety and a methoxy group. The presence of a methoxy group was confirmed by the HMBC correlation between H-OMe ( δ H 3.70) and C-6 ( δ C 161.87) suggesting that the methoxy is located at C-6.…”
Section: Resultsmentioning
confidence: 67%
“…[ 2 ] The major identified constituents in Dryopteris genus are phenols, flavonoids, and terpenoids. [ 3 4 5 ] In a previous study, the chemical constituents of 18 Dryopteris genus were investigated and compared. [ 6 ] However, only few studies of chemical constituents of D. erythrosora have been conducted so far.…”
Section: Introductionmentioning
confidence: 99%
“…44 Another study reported that 4 exhibited cytotoxic activities against human lung cancer (A549), human breast cancer cell (MCF7) and human liver cancer (HepG2) with IC 50 values of 5.25, 8.58 and 4.76 µM, respectively. 45 Moreover, 4 showed cytotoxicity against colon cancer (HCT116) cells with an IC 50 value of 10% at 100 ppm. 46 Compound 4 from Artemisia argyi, artemisinin from Artemisia annua, and the latter's semi-synthethic derivative, artesunate, showed the greatest activity in in vitro cytotoxicity tests against HCT116 colon adenocarcinoma cell line, with IC 50 values ranging in concentration from micromolar to millimolar amounts.…”
Section: Results and Discusionmentioning
confidence: 99%